Nutrients and Mother’s Diet in the Epigenetic Regulation of Placenta - Iván Enrique Naranjo Logroño; Anthony Alfonso Naranjo Coronel; Cristian Alberto Zumárraga Pozo; María Belén Peñaherrera Lema (ESPOCH Congresses, 2021)
Abstract Introduction: Pregnancy was defined as a state that exposes women to multiple anatomical-physiological, biochemical, psychological, and adaptive genomic changes in an environment of homeostatic balance and preparation of the fetus in the external environment. From fertilization to birth, a genetic program previously imprinted in your cells had been developed, which was influenced by the state of maternal health, preconception, nutritional factors, and the diet of the pregnant woman. Other secondary ones were of the maternal-fetal hormonal type, stress, toxic, viral or bacterial infections. Objective: To describe the influence of nutrition and maternal diet as factors of change in the epigenetic regulation of the placenta and in the perinatal results. Methods: Academic Google, Scopus, PubMed, ClinicalKey databases were searched using MeSH and DeCS terms: `epigenetics', `placent', `diet', `pregnancy', `imprint'. Discussion: Methylation of deoxyribonucleic acid (DNA) was the common way for epigenetic expression to take place and could be demonstrated in tissues. Observations highlight differences in placental tissue and the existence of hypo-methylation zones of DNA that resemble those present in malignant cells, the placenta being very sensitive to epigenetic marks and to maternal and fetal signals that allow its adaptation or depress influences from the environment. Conclusion: The placenta had unique genomic characteristics and was a reactive tissue to internal and external influences that had great clinical importance for fetal growth, appearance of neural tube defects, development of diabetes, high blood pressure, obesity, and other extrauterine diseases.